Donor-derived PLA2R-positive membranous nephropathy after post-mortal kidney transplantation: exceptional case - Baarz, Bastian Robinson; Jochims, Jan Alexander; Unterwalder, Nadine; Amann, Kerstin; Eckardt, Kai-Uwe; Choi, Mira (Clinical kidney journal, 2025)
Donor-derived glomerular diseases after organ transplantation are rare and may be challenging to diagnose. We report two kidney transplant recipients from a deceased donor with previously undiagnosed phospholipase A2 receptor (PLA2R)-positive membranous nephropathy (MN). Recipient 1 experienced delayed graft function with gross albuminuria; biopsy showed PLA2R-positive MN. Recipient 2 had immediate graft function. In both patients anti-PLA2R sera were negative, while retrospective donor testing confirmed an anti-PLA2R titer, suggesting donor-derived idiopathic MN. Follow-up under standard immunosuppression showed improving creatinine and partial remission of albuminuria in Recipient 1, and stable function with modest, transient albuminuria in Recipient 2. Thus, kidneys from donors with MN can yield acceptable outcomes.
Online veröffentlicht: 22. Oktober 2025
Gesehen am 04.12.2025